GERAKAN SOSIAL PANDAWARA GROUP UNTUK EKONOMI BIRU DAN KEBERLANJUTAN PESISIR PANTAI INDONESIA - Saputra, Emon (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the impact of the Pandawara Group social movement in supporting the blue economy and the sustainability of coastal ecosystems in Indonesia. The research employs a qualitative approach with a case study method, collecting data through literature review and document analysis from various sources. The study results indicate that the Pandawara Group successfully mobilized public support and engaged multiple stakeholders, including the private sector and government, in collective actions to clean up coastal areas and sustainably manage marine waste. The discussion reveals that this movement's success not only contributes to environmental cleanliness but also serves as an inspirational model for strengthening cross-sector collaboration. The conclusion of this study is that the Pandawara Group demonstrates significant potential as an example for other social movements in supporting the blue economy and raising public awareness of the importance of marine ecosystem conservation.